The implications of low quality bicycle paths on the gaze behaviour of young learner cyclists. (July 2017) - Vansteenkiste, Pieter; Zeuwts, Linus; van Maarseveen, Mariëtte; Cardon, Greet; Savelsbergh, Geert; Lenoir, Matthieu
Highlights: Children look less to the road and more to task irrelevant regions than adults. Children nor adults cycle slower on low quality cycling track. No overall difference in fixation frequency or duration between adults and children. Low quality road did not affect gaze behaviour of children more than that of adults. Abstract: In a recent study, Vansteenkiste et al. (2014) described how low quality bicycle paths cause an apparent shift of visual attention from distant environmental regions to more proximate road properties. Surprisingly, this shift of visual attention was not accompanied by an adaptation in cycling speed. The current experiment investigated to what extent these findings are applicable for young learner bicyclists (aged 6–12 years). Since young learner bicyclists do not yet have mature visual and motor skills, it was expected that the implications of a poor road surface would be larger for them than for experienced adult bicyclists. In general, children looked less to the road and more to task irrelevant regions, but the magnitude of the shift of visual attention when cycling on a low quality bicycle track was similar to that of adults. Although children cycled slower than adults, they did not cycle slower on the low quality track compared to the high quality track. Overall, our results suggest that children displayed a different visual-motor strategy than adults, characterized by lower cycling speeds and a different visual behaviour, and that they responded in a similar way to a low quality bicycle path as adults.